Kajian Folklor: Tembang Dolanan “E Dayohe Teko” Sebagai Refleksi Masalah Kehidupan - Desi Tri Utami; Muh Akbar Kurniawan (Mathematics Education Study Program, 2025)
Reflection on life problems is a stage for exploring a human's actions and experiences in everyday life. This reflection process can be taken from various sources including tembang dolanan. The tembang dolanan